Khủng hoảng tài chính thế giới và khả năng sinh lời của ngân hàng thương mại Việt Nam: Cách tiếp cận theo phương pháp Bayes - Phạm Hải, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This paper aims to investigate the impact of the global financial crisis, internal and external factors on profitability of commercial banks in Vietnam. By employing the data from of 30 Vietnamese commercial banks and macroeconomic factors from the period 2007 to 2018, and the Bayesian approach, Gibbs sampling as well, this paper finds that financial crisis, bank size, bank capital, liquidity assets, customer deposit, bank loans have positive impacts on bank profitability. Factors that have opposite effects are loan loss provision, interest expense, operating expense.
Keywords: Profitability; Bayes; Financial crisis; Commercial bank